Mechanical Behavior of High-Strength Bolted Joints Fabricated from Fire-Resistant Steel at Elevated Temperatures - Yuedong Wang; Xiaorun Li; Peng Liu; Changdong Wu; Chuhan Liu; Lijing Zeng; Wentao He; Tiantian Yin (Advances in Materials Science and Engineering)
The use of fire-resistant steel is an effective way to alleviate fire safety issues in steel structures. Considering the limited research on bolted joints fabricated from fire-resistant steel, this study presents the results of the experimental investigation on the mechanical behavior of 40 specimens of bolted joints at room temperature and elevated temperatures (20°C∼700°C). These specimens are assembled with fire-resistant steel plates and fire-resistant high-strength bolts (or ordinary high-strength bolts). The mechanical behavior of these specimens was investigated, which included the failure mode, deformation performance, and degradation of bearing capacity. The experimental results show that the treatment of the friction surface (specifically, impeller blasting and sprayed hard quartz sand) has a negligible effect on the ultimate strength of specimens and a relatively significant effect on the slip strength. In addition, reduction factors of the tensile strength (KN) and slip strength (KS) for both fire-resistant bolt specimens and ordinary high-strength bolt specimens decrease with the increase in temperature, especially in the case of elevated temperatures ranging from 400°C to 700°C. Prediction models with different reliability degrees are proposed to calculate the degradation of tensile strength under elevated temperatures, which has the potential to be used for the fire-resistant design of steel connections and structures.